Fork it, let's eat well - Chia, Denise Wei Lin (Nanyang Technological University, 2023)
The Fork It, Let’s Eat Well campaign aims to start vital dialogues with Singaporean youths on nutrition and proper eating through weekly roadshow campaigns around schools as well as by offering a digital resource for youths and their parents who are keen to learn more about nutrition and diets. The objective of this project is to provide Singaporean youths with the information and resources they need to lead a healthy lifestyle and make better dietary decisions. The campaign aims to inform youths on the principles of nutrition and healthy eating as well as to address the growing health issues among their daily choices. The author hopes to empower youths to take control of their daily consumption wellbeing and set them on a path towards a healthier future.